Hubungan antara Citra Tubuh dengan Kepercayaan Diri pada Wanita Pengguna Make-Up (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Individuals who are satisfied with their bodies and aware of their ideal body shape will form a positive body image, indirectly shaping their self-confidence. Confidence is assessing oneself and the objects around it so that individuals have confidence that they can do something according to their abilities. At the same time, body image is an assessment of the size, shape, and body assessment based on individual evaluations and affective experiences related to their physical attributes. This study aims to determine the relationship between body image and self-confidence in women who use make-up in Sumber Harum Village, Tungkal Jaya District. The subjects used in this study were adult women who use make-up, namely female students, workers, and housewives (IRT) aged 20-40 years. The results of the multiple regression test for self-confidence and body image variables were an R-value of 0.558 and an R Squeare value of 0.307 with a p-value = 0.000. This shows a relationship between body image and self-confidence in adult women who use make-up in Sumber Harum Village, Tungkal Jaya District, 31.2%. The standardized beta coefficient of confidence normality test results showed a significance of 0.851 (p> 0.05). It can be stated that the data is usually distributed. The standardized beta coefficient of body image obtained a significance value of 0.464 (p > 0.05), so it can be stated that it is usually distributed.